ANALISIS GERAKAN MATA UNTUK DETEKSI ALZHEIMER: STUDI KOMPARATIF LIMA METODE UTAMA - Ziegel, Dennis Jusuf; Indra, Evta (Politeknik Bisnis Indonesia, 2024)
In the digital era, eye-tracking technology has emerged as a valuable non-invasive tool for assessing neurological and cognitive functions. This review explores five key methods for evaluating Alzheimer’s Disease (AD) using eye-tracking: fixation and saccade analysis, pupil size measurement, task-specific eye-tracking, reading task analysis, and novelty preference scores. Fixation and saccade metrics reveal significant disruptions in visual scanning and information processing in AD patients, characterized by longer fixation durations and reduced saccade frequency. Pupil size measurements indicate diminished cognitive load and emotional responsiveness. Task-specific eye-tracking, including tasks such as image description, shows difficulties in maintaining focus and interpreting visual stimuli. Reading task analysis highlights increased fixation durations and backward saccades, reflecting challenges in text comprehension and information retention. Novelty preference scores suggest reduced interest in new stimuli, correlating with cognitive decline. These findings underscore the potential of eye-tracking metrics for early detection and monitoring of AD, though variability in eye movement patterns and additional factors like sleep disorders emphasize the need for comprehensive diagnostic approaches.